Climate of submontane location Stará Lesná (1988–2013) - BIČÁROVÁ, Svetlana; MAČUTEK, Jozef; BILČÍK, Dušan (Contributions to Geophysics and Geodesy, 2014)
This paper focuses on evaluation of climatic data obtained at Meteorological Observatory GPI SAS Stará Lesná according to the classical daily observations carried out for period 1988-2013. Location is situated at the foothills of the High Tatra Mts. and represents submontane climate zone favourable for temperate coniferous and mixed forest vegetation. According to observations climate of Star´a Lesn´a is characterized by average annual air temperature 5.9 °C that seasonally varies from –3.5 °C (DJF) to 15.2 °C (JJA). Air-temperature extremes range between –26.5 and 34.2 °C. Daily air temperature maxima and derived indices such as the number of summer days indicate moderate warming during last decade. Growing season length is about 195 days. Average annual precipitation is 744 mm, seasonal comparison shows nearly twice more precipitation amount in summer than winter half year. Snow depth is 35 cm on average, extraordinary over 50 cm. Relative air humidity is about 78%. Wet periods lasted from 5 to 13 consecutive wet days; substantially longer are dry periods from 14 to 39 days. Average sunshine duration is 1806 hours per year. The number of sunny days is clearly lower than the number of cloudy days. Surface air pressure 920.4 hPa relates to altitudinal position of site. Wind blows mostly from the more open southern side. Although average wind speed is rather low (2.1 m/s), occurrence of strong wind gusts above 40 m/s can cause such a spatial destruction of natural environment as in November 2004.